Computational Model of DIC Microscopy for Reconstructing 3-D Specimens - Kagalwala, F.; Lanni, F.; Kanade, T. (Methods of Information in Medicine, 2000)
Differential Interference Contrast (DIC) microscopy is a powerful visualization tool used to study live biological cells. Its use, however, has been limited to qualitative observations. The inherent non-linear relation between the object properties and the image intensity makes quantitative analysis difficult. As a first step towards measuring optical properties of objects from DIC images, we develop a model for the image formation process using methods consistent with energy conservation laws. We verify our model by comparing real image data of manufactured specimens to simulated images of virtual objects. As the next step, we plan to use this model to reconstruct the three-dimensional properties of unknown specimens.
Keywords: Optical Microscopy; Light-propagation Model; Differential Interference Contrast